Epilepsi dan Attention-Deficit / Hyperactivity Disorder (ADHD) pada Anak - Riki Sukiandra (Jurnal Ilmu Kedokteran, 2016)
Attention-deficit / hyperactivity disorder (ADHD) has been associated with childhood epilepsy. Epilepsy are themost common neurologic disturbance in child age. Children with epilepsy tend to get one or more ADHD symptoms,its related to lack of norepinephrine neurotransmitter in brain, that cause attenuate the effect of GABA and disruptionto fronto-striatal brain networks, these same brain networks are disrupted by seizures or the structural brainabnormalities that can cause seizures. Children with epilepsy especially absance, tend to get inattentive type ofADHD more than other types. Abnormalities of electro-encephalography found in inattentive type of ADHD withhigh focus activities in all lobe area. No data published that methylphenidate can lower seizure threshold or act asproconvulsant. Children with epilepsy tend to get one or more symptoms of ADHD in the following days.